Religious Character Development through GASMI Pencak Silat Activities at Ar Rahman Mosque in North Metro District - Ganjar Robi Sayekti; Irhamudin Irhamudin; Marzia Khatan Smita; Adi Wijaya; Novi Ayu Kristiana Dewi (Bulletin of Pedagogical Research, 2026)
This study aims to analyze the process of religious character development among students through GASMI martial arts training at Ar-Rohman Mosque, North Metro District, and to identify the supporting and inhibiting factors affecting its implementation. The study was motivated by preliminary findings indicating that some students exhibited limited religious understanding, weak ethical behavior, and low discipline prior to participating in GASMI training. A qualitative approach with a descriptive field research design was employed. Data were collected through observation, in-depth interviews, and documentation involving fifteen students selected through purposive sampling based on their limited religious background before joining the training program. The findings indicate that religious character development is fostered through the integration of religious practices into martial arts training activities. These practices include routine prayers before training sessions, participation in congregational prayers, weekly religious studies, fasting before level advancement examinations, and the application of educational sanctions, such as reciting the adhan or selected Qur’anic verses, for students who violate training regulations. Thematic analysis revealed the enhancement of several dimensions of religious character, including discipline, responsibility, independence, honesty, cooperation, humility, courage, and patience. The results demonstrate that GASMI martial arts training serves not only as a means of physical development but also as an effective medium for the internalization of Islamic values. This study concludes that a religiously oriented martial arts training model makes a significant contribution to the development of students’ religious character. It also recommends further research to examine its applicability and effectiveness in broader educational and community settings.